2016
DOI: 10.5539/res.v8n2p210
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between the Spiritual Intelligence, Self-Control, and Life Satisfaction in High School Teachers of Mahshahr City

Abstract: This study aims to investigate the relationship between the spiritual intelligence, self-control, and life satisfaction in high school teachers of Mahshahr city. To this end, 253 people of all high school teachers in Mahshahr city were selected as the sample using the multistage cluster sampling method. For data collection, King's (2008) spiritual intelligence questionnaire, Schneider's self-control questionnaire and Diener et al. (1985) life satisfaction questionnaire were used. For data analysis, Pearson's … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 8 publications
0
5
1
1
Order By: Relevance
“…In contrast, life satisfaction has a weak association with spiritual intelligence, which implies that nurses who generally consider their life to be successful likely lack the abilities and behaviour capabilities required to apply spirituality. This finding challenges other research [ 48 , 49 , 50 ] that found that spiritual intelligence and its components enable people to think deeply about the spiritual considerations, use resources to address difficulties in their lives and act morally [ 51 ], all of which boost life satisfaction. Spiritual intelligence fosters internal harmony and enables nurses to appreciate the enjoyable side of life [ 48 ].…”
Section: Discussioncontrasting
confidence: 91%
“…In contrast, life satisfaction has a weak association with spiritual intelligence, which implies that nurses who generally consider their life to be successful likely lack the abilities and behaviour capabilities required to apply spirituality. This finding challenges other research [ 48 , 49 , 50 ] that found that spiritual intelligence and its components enable people to think deeply about the spiritual considerations, use resources to address difficulties in their lives and act morally [ 51 ], all of which boost life satisfaction. Spiritual intelligence fosters internal harmony and enables nurses to appreciate the enjoyable side of life [ 48 ].…”
Section: Discussioncontrasting
confidence: 91%
“…Many findings also reveal no direct relationship between SI and satisfaction. Bigdeloo and Bozorgi ( 2016 ) have indicated that SI and self-control, together, can predict life satisfaction in high school teachers. Likewise, Munawar and Omama Tariq ( 2018 ) reported a significant correlation between spiritual intelligence, religiosity, and life satisfaction among elderly Pakistani Muslim people.…”
Section: Si In Relation To Well-beingmentioning
confidence: 99%
“…Munawar and Omama Tariq (2018), Kumawat and Puri (2019) suggest that there is life satisfaction and spiritual intelligence between a positive relationship. Bigdeloo and Bozorgi (2016) reported that there are positive and significant relationships between life satisfaction and spiritual intelligence and that spiritual intelligence can predict life satisfaction. Spirituality intelligence helps to resilience in people who experience stress (Khosravi & Nikmanesh, 2014).…”
Section: Discussionmentioning
confidence: 99%